Piper sarmentosum Roxb. methanolic extract prevents stress-induced gastric ulcer by modulating oxidative stress and inflammation - Akmal, Muhamad Nurul; Abdel Aziz, Ibrahim; Nur Azlina, Mohd Fahami (Frontiers in Pharmacology, 2023)
This study investigated the gastroprotective effect of Piper sarmentosum (PS) on stress-induced gastric ulcers in rats by measuring its effect on oxidative stress, gastric mucosal nitric oxide (NO), and inflammatory biomarkers. Twenty-eight male Wistar rats were randomly divided into four groups; two control groups (non-stress and stress) and two treated groups supplemented with either methanolic PS extract (500 mg/kg body weight) or omeprazole (OMZ; 20 mg/kg) orally. After 28 days of treatment, the stress control, PS, and OMZ groups were subjected to water-immersion restrain stress (WIRS) for 3.5 h. Gastric tissue malondialdehyde (MDA), NO, superoxide dismutase (SOD), inducible NO synthase (iNOS), SOD mRNA, tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and IL-6 levels were measured. WIRS significantly increased gastric MDA, NO, and pro-inflammatory cytokine levels compared to the non-stressed control group. PS and omeprazole supplementation significantly reduced WIRS-exposure-induced gastric ulcers and MDA, iNOS, and IL-1β levels. However, only PS reduced NO, TNF-α, and IL-6 levels, which were upregulated in this ulcer model. In conclusion, the gastroprotection afforded by PS is possibly mediated by gastric mucosal NO normalization through reduced iNOS expression and attenuation of inflammatory cytokines. PS showed a greater protective effect than omeprazole in reducing gastric lesions and NO, TNF-α, and IL-6 levels, and iNOS expression.